Biological science - James L Gould (W. W. Norton, 1996)
The book is divined into 6 parts. Part 1: The chemical and cellular basics of life. Part 2: The perpetuation of life. Part 3: Evolutionary biology. Part 4: The genesis and diversity of organisms. Part 5: The biology of organisms. Part 6: Ecology